2018
DOI: 10.4103/ijo.ijo_1212_18
|View full text |Cite
|
Sign up to set email alerts
|

Management of recurrent rhegmatogenous retinal detachment

Abstract: Rhegmatogenous retinal detachment (RRD) repair is one of the most common vitreoretinal surgeries a surgeon performs. In an ideal scenario, RRD can be repaired with a single surgical intervention; however, despite excellent skill, flawless technique, and the introduction of high-end technology, up to 10% of cases require additional interventions to ultimately repair recurrent detachments. It is thus important to study the outcomes of multiple interventions to understand whether performing repeat vitrectomy on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 75 publications
0
37
0
4
Order By: Relevance
“…The rates of recurrent RDs in the literature ranged between 5 and 31.4% [20]. In our study, 10 patients had a recurrent RD, representing 11.8% of the population, 2 of which were from the 1000cs group (4.7% of the group) while 8 were from the 5000cs group (19% of the group).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The rates of recurrent RDs in the literature ranged between 5 and 31.4% [20]. In our study, 10 patients had a recurrent RD, representing 11.8% of the population, 2 of which were from the 1000cs group (4.7% of the group) while 8 were from the 5000cs group (19% of the group).…”
Section: Discussionmentioning
confidence: 47%
“…Despite some documented negative features, silicone oil remains the most compatible material for vitreous replacement [18]. Studies have not shown a difference in the tamponading force of various silicone oils, and selecting the proper oil for clinical use remains controversial [19][20][21]. Early postoperative rise in IOP is common after PPV with silicone oil injection and may be related to anterior chamber inflammatory activity or obstruction to aqueous flow by choroidal effusion or both [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous series, the anatomical success rate of 20-gauge vitrectomy in RRD patients with PVR was reported between 51% and 80%. [1,2,5,6] In the study by Iwahashi-Shime et al [1] the anatomical and functional outcomes of 25-gauge vitrectomy in 27 RRD patients with PVR were evaluated. The mean follow-up period of the study was 32.5 months, which was quite longer than our study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] As PVR usually causes significant vitreoretinal traction over the retina, vitrectomy is a valuable option in the treatment of the RD cases associated with PVR. [3][4][5][6][7] PVR is divided into three stages as stage A, B and C. [8] Stage C PVR is characterized with visible preretinal and subretinal membranes or retinal foreshortening. [8] Sophisticated vitreoretinal maneuvers, such as membrane peeling and retinotomy/retinectomy, which may be performed only during vitrectomy are usually required in cases with PVR.…”
mentioning
confidence: 99%
“…4 Additionally, RD is considered a true ophthalmologic emergency and may require immediate surgical intervention to prevent irreversible vision loss. 5,6 A thorough history and physical examination including biomicroscopy with slit lamp and measurement of intraocular pressures is often needed. Proper assessment of a patient with presumed retinal detachment requires a clear view to the posterior segment of the eye.…”
Section: Introductionmentioning
confidence: 99%